2018
DOI: 10.1002/geo2.50
|View full text |Cite
|
Sign up to set email alerts
|

Human migration to the forest frontier: Implications for land use change and conservation management

Abstract: Human migration is often considered an important driver of land use change and a threat to protected area integrity, but the reasons for in‐migration, the effectiveness of conservation restrictions at stemming migration, and the extent to which migrants disproportionately contribute to land use change has been poorly studied, especially at fine spatial scales. Using a case study in eastern Madagascar (603 household surveys, mapping agricultural land for a subset of 167 households, and 49 focus group discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 67 publications
1
22
0
5
Order By: Relevance
“…However, we did find that shade-levels are higher for those farms in the buffer and are aware that farmers in this area are dependent on a poorly maintained road to access the closest market and are predominantly migrants. It is common among recently established protected areas to find the most recent migrants located in the former forest frontier [18]. Therefore, since we found that being a migrant alone was not a predictor of a farmer's vulnerability across the study communities, our findings suggest the location of a farm in the landscape was more influential.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, we did find that shade-levels are higher for those farms in the buffer and are aware that farmers in this area are dependent on a poorly maintained road to access the closest market and are predominantly migrants. It is common among recently established protected areas to find the most recent migrants located in the former forest frontier [18]. Therefore, since we found that being a migrant alone was not a predictor of a farmer's vulnerability across the study communities, our findings suggest the location of a farm in the landscape was more influential.…”
Section: Discussionmentioning
confidence: 53%
“…Freidman et al [17], for example, highlight how, in Ghana's cocoa sector, the structure of gender relations shape patterns of vulnerability, playing a central role in determining women's access to land and non-farm opportunities. The establishment of protected areas can also have an impact on the ability of local communities to respond to climate shocks, particularly for relatively recent migrants who are often located along former forest frontiers [18]. As Mclaughlin and Dietz [19] note, much of the literature on vulnerability has tended to focus on socially-mediated structures (especially economic and political) and their role in environmental degradation, rather than considering social and ecological phenomena as integrated and mutually constitutive.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from birth rates, domestic immigration triggered by recent price booms in major cash crops (vanilla and cloves) may accelerate population growth in the region (Hänke et al 2018;Zhu 2018). So far, Jones et al (2018) documented only rather local migratory trends in the southern part of the study area (< 50 km movements reported by about 90% of interviewed households from the Ankeniheny-Zahamena Corridor). These short distance movements were mainly driven by the search for accessible lands (Jones et al 2018).…”
Section: Settlement Development and Determinantsmentioning
confidence: 90%
“…So far, Jones et al (2018) documented only rather local migratory trends in the southern part of the study area (< 50 km movements reported by about 90% of interviewed households from the Ankeniheny-Zahamena Corridor). These short distance movements were mainly driven by the search for accessible lands (Jones et al 2018). At least one fifth of all villages in our study area were newly established since 1990 in areas that were still forested at that time.…”
Section: Settlement Development and Determinantsmentioning
confidence: 90%
“…Unfortunately, there are two significant challenges to resolving the tenure of farmers on Madagascar's forest frontier. First, although mature tree fallows are locally considered part of agricultural land, the current forest code does not allow formal tenure to be granted over such land as it is considered to be state land (Jones et al, 2018 Manuscript to be reviewed 2006-031), those living within the border of protected areas, i.e. many of those considered in this study, are not eligible to formalize their tenure.…”
Section: Can Forest Conservation In Low-income Countries Be Achieved mentioning
confidence: 99%